Trends in the Prevalence and Antibiotic Resistance of Non-tuberculous Mycobacteria in Mainland China, 2000–2019: Systematic Review and Meta-Analysis - Lei Zhou (Frontiers in Public Health, 2020)
Background: China is a high-burden country of tuberculosis. The proportion of diseases caused by non-tuberculous mycobacteria (NTM) has increased, seriously affecting the prevention, control, and management of tuberculosis (TB) and posing a significant threat to human health. However, there is a lack of an organized monitoring system for NTM such as that used for tuberculosis. Comprehensive data on patient susceptibility, dominant species, and drug resistance profiles are needed to improve the treatment protocols and the management of NTM.Methods: Primary research reports of NTM clinical specimens from mainland China published between January 1, 2000 and May 31, 2019 were retrieved from four online resources (BIOSIS, Embase, PubMed, and Web of Science) and three Chinese medical literature databases (CNKI, Wanfang, and Vip) as the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Results: In total, 339 publications were included in the systematic review, 129 were used in the drug susceptibility analysis, and 95 were used in the meta-analysis. Traditional culture using Lowenstein–Jensen slants combined with P-nitrobenzene acid and thiophene-2-carboxylic acid hydrazine differential medium and proportional method was most commonly used for the isolation, identification, and drug susceptibility testing of NTM in China. The crude isolation rate for NTM among TB suspected cases was 4.66–5.78%, while the proportion of NTM among Mycobacterium isolates was 11.57%. Mycobacterium abscessus and Mycobacterium avium complex were the most common clinical NTM species. NTM only showed general sensitivity to ethambutol, linezolid, clofazimine, amikacin, tobramycin, and clarithromycin.Conclusions: The prevalence of NTM in China has shown a decreasing trend. M. abscessus was replaced as the dominant species by Mycobacterium intracellulare over the course of the study. The geographic diversity of different species showed the effects of environmental and economic factors on the distribution of NTM and indicated that there were important factors still not identified. While there were only a limited number of antibiotics to which NTM showed any sensitivity, the drug resistance profiles of the isolates were highly variable and thus more caution should be taken when empirically treating NTM infection.